2016
DOI: 10.1051/0004-6361/201628711
|View full text |Cite
|
Sign up to set email alerts
|

Compton-thick AGN in the 70-monthSwift-BAT All-Sky Hard X-ray Survey: A Bayesian approach

Abstract: The 70-month Swift/BAT catalogue provides a sensitive view of the extragalactic X-ray sky at hard energies (>10 keV) containing about 800 active galactic nuclei (AGN). We explore its content in heavily obscured, Compton-thick AGN by combining the BAT (14-195 keV) with the lower energy XRT (0.3-10 keV) data. We apply a Bayesian methodology using Markov chains to estimate the exact probability distribution of the column density for each source. We find 53 possible Compton-thick sources (probability range 3 -100%… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
48
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 69 publications
14
48
1
Order By: Relevance
“…Also shown are the recent constraints from Akylas et al (2016) on the luminosity function of Compton-thick AGNs using the 70-month Swift-BAT all-sky survey hard X-ray catalogue. The Akylas et al (2016) space densities are lower than previous studies, including those from Ajello et al (2012). This discrepancy is surprising, given that the two studies find very similar observed fractions of Compton-thick sources among the total AGN sample.…”
Section: X-ray Agn Obscuration Distributioncontrasting
confidence: 76%
See 1 more Smart Citation
“…Also shown are the recent constraints from Akylas et al (2016) on the luminosity function of Compton-thick AGNs using the 70-month Swift-BAT all-sky survey hard X-ray catalogue. The Akylas et al (2016) space densities are lower than previous studies, including those from Ajello et al (2012). This discrepancy is surprising, given that the two studies find very similar observed fractions of Compton-thick sources among the total AGN sample.…”
Section: X-ray Agn Obscuration Distributioncontrasting
confidence: 76%
“…The number of Compton-thick sources among AGNs is still debated with different studies finding discrepant results in terms of both space density and cosmological evolution (e.g. Brightman & Ueda 2012;Ueda et al 2014;Ricci et al 2015;Buchner et al 2015;Akylas et al 2016).…”
mentioning
confidence: 99%
“…The prevalence of CTK AGNs is predicted by population-synthesis models of the cosmic X-ray background, although these models have significant uncertainties in the regime of very high N H (e.g., Gilli et al 2007;Ueda et al 2014). The predicted total X-ray emission from CTK AGNs is usually less than that from other AGNs (e.g., Gilli et al 2007;Treister et al 2009; also see Buchner et al 2015, for relevant spectral fitting), consistent with the very hard X-ray (10 keV) observations of the local universe (e.g., Akylas et al 2016;Koss et al 2016). Even if these CTK AGNs predominantly reside in low-M * systems, the total L X from these galaxies will be at most the same as that from high-M * galaxies; the average L X in low-M * galaxies should be still much lower than for massive galaxies, as the former has much larger number density.…”
Section: Bhar/sfr Ratio As a Function Of M *supporting
confidence: 72%
“…From the Swift/BAT 70-month catalog (Baumgartner et al 2013), Ricci et al (submitted to ApJS) systematically analyze X-ray data below 10 keV obtained mainly with Swift/X-Ray Telescope (XRT) and XMM-Newton, which are combined with the Swift/BAT spectra in the 14-150 keV. As a result, Ricci et al (2015) identify 55 CTAGN candidates (see also Akylas et al 2016). However, since the photon statistics of the Swift/XRT spectrum is limited and the data above and below 10 keV were not simultaneously obtained (thus being affected by time variability), large uncertainties remain in the derived column density and intrinsic luminosity.…”
Section: Introductionmentioning
confidence: 99%